1999
DOI: 10.1002/(sici)1096-9888(199904)34:4<435::aid-jms803>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, primary structure characterization and identification of the glycosylation pattern of recombinant goldfish neurolin, a neuronal cell adhesion protein

Abstract: Neurolin is a growth-associated cell surface glycoprotein from goldÐsh and zebra Ðsh which has been shown to be involved in axonal path-Ðnding in the goldÐsh retina and suggested to function as a receptor for axon guidance molecules. Being a member of the immunoglobulin superfamily of cell adhesion proteins, neurolin consists of Ðve N-terminal extracellular immunoglobulin (Ig)-like domains, a transmembrane and a short cytoplasmatic domain. Repeated injections of polyclonal Fab fragments against neurolin and of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The immunoprecipitates from the other cell lines, although displaying slightly different molecular weights, were again identified as ALCAM/CD166. The differences in molecular weight are probably due to tissue specific variation in N-glycosylation pattern (Pourquié et al, 1992;Denziger et al, 1999).…”
Section: Isolation and Characterization Of The I/f8 Scfv Anti-alcam/cmentioning
confidence: 99%
“…The immunoprecipitates from the other cell lines, although displaying slightly different molecular weights, were again identified as ALCAM/CD166. The differences in molecular weight are probably due to tissue specific variation in N-glycosylation pattern (Pourquié et al, 1992;Denziger et al, 1999).…”
Section: Isolation and Characterization Of The I/f8 Scfv Anti-alcam/cmentioning
confidence: 99%
“…12 The molecular weight of ALCAM is 65 kDa but with N-glycosylation at 8 putative sites, the mature ALCAM molecule has a molecular weight of 110 kDa. 13 Five extracellular Ig domains, a transmembrane region and a short cytoplasmic tail make up the ALCAM protein that resembles E-cadherin in motif-arrangement. 12 ALCAM mediates both heterophilic (ALCAM-CD6) and homophilic (ALCAM-ALCAM) cellcell interactions.…”
mentioning
confidence: 99%
“…We could show that all six potential N-glycosylation sites of NCAM from adult mouse brain are modified, at least one of these (N-1) only partially. The differential approach employed here should be particularly valuable in the case of highly heterogeneous glycosylations as found for glycoproteins from different cellular systems and species [15,16,17,26,27,31,32,33,34,35,36,37,38,39,40]. Direct MALDI-TOF-MS studies of glycopeptides have shown pronounced heterogeneous structures on single N-glycosylation sites of NCAM [26].…”
Section: Discussionmentioning
confidence: 99%